1995
DOI: 10.1063/1.358936
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature ohmic contact to n-type 6H-SiC using nickel

Abstract: Specific contact resistances measured at elevated temperatures for Ni ohmic contacts to 6H-SiC were reported. The specific contact resistances were measured with the linear transmission line method at both room temperature and at 500 °C and yielded values <5×10−6 Ω cm2 at both temperatures. The trend shows a decreasing contact resistance at higher temperatures. The annealed metal film is a nickel silicide with substantial mixing of C throughout the silicide layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(74 citation statements)
references
References 5 publications
1
63
1
Order By: Relevance
“…We investigated Ni-based contacts, since Ni can be used as a mask for GaN plasma etching [13], and as a Schottky barrier to n-GaN [14]. In addition, Ni is usually used to form an ohmic contact to 6H-SiC, which is a highly suitable substrate material for the epitaxial growth of GaN [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…We investigated Ni-based contacts, since Ni can be used as a mask for GaN plasma etching [13], and as a Schottky barrier to n-GaN [14]. In addition, Ni is usually used to form an ohmic contact to 6H-SiC, which is a highly suitable substrate material for the epitaxial growth of GaN [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nickel, a widely used metal for ohmic contacts on n-type SiC, reacts with the underlying SiC to form Ni 2 Si at 500°C, but the contacts do not become ohmic until they are annealed at around 950°C. 4,5 Recently, Kurimoto et al 6 found that Ni silicides, composed of Ni 2 Si, NiSi, and NiSi 2 , are formed at 500°C in Ni/SiC, and the composition does not vary in the temperature region of 500-1100°C. Therefore, the formation of the silicide itself does not appear to be the critical factor in the formation of ohmic contacts.…”
Section: Introductionmentioning
confidence: 98%
“…8 One of the most common and highly researched metals used to form an ohmic contact to SiC is Ni. [9][10][11] While Ni is typically used as a contact to n-type SiC, it has also been demonstrated for use as a contact to p-type SiC. 12,13 Although Ni has shown the ability to provide a low specific contact resistance to SiC, the reaction products of the necessary high-temperature anneal, including carbon segregation during nickel silicide formation, have the potential to cause reliability problems.…”
Section: Introductionmentioning
confidence: 99%